Pengaruh Arus Kas Operasi, Laba Akuntansi, Current Ratio, Total Asset Turnover Terhadap Return Saham Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2017-2020 - Nelly Nattasyah Sagala; Deasy Arisandy Aruan; Jefry Sumonang Hendrikus Situmorang; Eben Ezer Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to understand the effect of operating cash flow, accounting profit, current ratio, total asset turnover on stock returns in consumer goods industrial sector companies listed on the IDX for the 2017-2020 period. This study uses a purposive sampling method with a population of 53 industrial sector companies. consumer goods listed on the Indonesia Stock Exchange for the period 2017-2020. The research sample is 120 data on the consumer goods industrial sector listed on the Indonesian stock exchange for the 2017-2020 period. The data investigation method used is multiple linear regression. The results of this study indicate that partially the accounting profit variable has a significant effect on stock return, but operating cash flow, current ratio and total asset turnover have no significant effect on stock return. Simultaneously, Operating Cash Flow, Accounting Profit, Current Ratio and Total Asset Turnover have a significant effect on stock returns in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Keywords: Operating Cash Flow, Accounting Profit, Current Ratio, Total Asset Turnover And Stock Return